Resistance of some tomato cultivars and rootstocks against Fusarium wilt pathogens (Damascus University Journal of agriculture sciences, 2025)
Fusarium wilt, caused by Fusarium oxysporum and Fusarium solani, is one of the most important diseases affecting tomatoes especially in greenhouses of Mediterranean Coast plain and fields in Syria. Twenty-four isolates of the pathogen were collected and purified from Tartous and Lattakia. They were classified on morphological and cultural characteristics. Their pathogenicity was evaluated towards the susceptible cultivar "Smertetra" according to the plant height, shoot and ro0ot dry weight, disease incidence % and disease severity %. Nine isolates belonging to the type Fusarium solani and 15 isolates belonging to the type Fusarium oxysporum. Two isolates were selected, the most virulent FU6 (Fusarium solani) and FU7 (Fusarium oxysporum), the disease severities of which were 56.7% and 73.3%, respectively. A test of the susceptibility of 21 locally grown tomato cultivars and hybrids, in addition to 8 rootstocks of Solanum lycopersicum L., to Fusarium wilt was calculated, based on a standard scale from 1 to 5 degrees. The cultivars varied in their susceptibility to infection with the tested isolates under conditions of artificial infection. The average of disease severity with FU7 isolate ranged between 0 and 53.33%. The following, respectively: Magdalina, Mandalon, Rossi, 388, 175, Red Guard, Kiswani 402, Dalal, Bastona, 258, Raya and significant differences with the rest of the local crosses. However, the disease severity with FU6 isolate ranged between 0 and 56.68%. The two cultivars that were most resistant to the infection were Balhi Chocolate and Magdalina, where the severity and the infection rate were 0%, and they achieved apparent differences with the cultivars: Mandalon, Rossi, Bastona, 175, 388, Kiswani 402, Kiswani 400, Randala, Raya, but with the rest of the cultivars and hybrids, the differences were Significant. As for rootstocks, there were no significant differences between them in the severity of infection with the pathogen, and  Multifort F1 was the best with an infection rate of 0%, and  Beaufort F1 was the most susceptible with an infection rate of 41.67% for both fungal isolates, while the rest of the rootstocks were graded as moderately resistant (MR) to moderate susceptible (MS).
Keywords: Fusarium wilt; Fusarium oxysporum; Fusarium solani; resistant cultivars; wild rootstocks